2011
DOI: 10.1007/s13157-011-0156-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Microtopography on Hydrology, Physicochemistry, and Vegetation in a Tidal Swamp of the Hudson River

Abstract: Hudson River freshwater tidal swamps have dynamic flooding and oxygenation regimes due to daily tidal flushing. Microtopography, small scale differences in elevation, adds even more complexity to inundation patterns and may have important implications for nutrient flow and wetland plant communities. The objective of this study was to determine if differences in inundation between microtopographic features were sufficient to alter physical, chemical, and biological attributes. Microtopography significantly affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
56
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 38 publications
2
56
1
2
Order By: Relevance
“…Similar results have been obtained in studies that compared the effects of contour bench terrace systems in the semiarid Negev in Israel (Stavi et al, 2015), examined terrace characteristics (Engdawork and Bork, 2014), and detected the impact of restoring degraded terraces (LaFevor, 2014). Previous works have reported that approximately 20% (to a potential 200%) of total surface rainwater could infiltrate into underground soil layers after terracing (Courtwright and Findlay, 2011), and that 1.13 times more rainfall can be stored in a terraced system than that in sloping land (Li et al, 2012). The low REW indicated that the study area is under severe water stress, whereas the large difference between the two sites (113.1% more REW in the terrace site) suggested that the construction of terraces could help to increase soil water content.…”
Section: Effects Of Terracing On Soil Water Rechargesupporting
confidence: 77%
See 1 more Smart Citation
“…Similar results have been obtained in studies that compared the effects of contour bench terrace systems in the semiarid Negev in Israel (Stavi et al, 2015), examined terrace characteristics (Engdawork and Bork, 2014), and detected the impact of restoring degraded terraces (LaFevor, 2014). Previous works have reported that approximately 20% (to a potential 200%) of total surface rainwater could infiltrate into underground soil layers after terracing (Courtwright and Findlay, 2011), and that 1.13 times more rainfall can be stored in a terraced system than that in sloping land (Li et al, 2012). The low REW indicated that the study area is under severe water stress, whereas the large difference between the two sites (113.1% more REW in the terrace site) suggested that the construction of terraces could help to increase soil water content.…”
Section: Effects Of Terracing On Soil Water Rechargesupporting
confidence: 77%
“…Terracing has been established as the main measure for soil and water conservation for fields with gradients under 25 • (Li et al, 2011;Liu et al, 2013). Terracing in such locations can reduce both flood runoff and the sediment transport modulus (Bai et al, 2015;Li et al, 2014a), and improve soil water conditions noticeably (Courtwright and Findlay, 2011;Huo and Zhu, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Similar results have 194 been obtained in studies that compared the effects of contour bench terrace systems in the 195 semiarid Negev in Israel (Stavi et al, 2015), examined terrace characteristics (Engdawork and 196 Bork, 2014), and detected the impact of restoring degraded terraces (LaFevor, 2014). Previous 197 works have reported that approximately 20% (to a potential 200%) of total surface rainwater 198 could infiltrate into underground soil layers after terracing (Courtwright and Findlay, 2011), and 199 that 1.13 times more rainfall can be stored in a terraced system than that in sloping land (Li et al, 200 2012a). The low REW indicated that the study area is under severe water stress, whereas the 201 large difference between the two sites (113.1 % more REW in the terrace site) suggested that the 202 construction of terraces could help increase soil water content.…”
supporting
confidence: 58%
“…Wetlands provide important ecosystem services, such as erosion control, water quality improvement, and fisheries and wildlife habitat protection, while supporting economic activities such as livestock grazing and medicinal plants collection [1][2][3]. Wetland plant communities vary spatially and temporally with interspecific competition [4], microtopography [5], soil [6], climate [7], management [8], and particularly, water regime [9][10][11]. In shallow lakes, water level fluctuations are a decisive element in the water regime, which is determined by water depth and the rate, duration, frequency, amplitude, and timing of flood or draw-down events [12,13].…”
Section: Introductionmentioning
confidence: 99%